Guarantee’s Right In Marriage By Perspective Of Women’s Study: A Gender Perspective - Abdilah, Nadhruna'im; Yuni, Kusnul Ciptanila (Faculty of Shariah UIN Ponorogo, 2024)
Departing from the shift in the meaning of ijbar which is identified with ikrah by most Indonesian people, especially in the gender perspective, the center for women's studies UIN Sunan Kalijaga, encourages researchers to conduct a study on the development of the implementation of ijbar rights in Indonesia today as well as legal regulations regarding the implementation of ijbar rights in marriage which are still a tradition in Indonesia and legal protection for women's human rights that have been degraded as a result of forced marriage as a consequence of the application of ijbar in a marriage. The type of research used is field research with a legal-formal approach. The results showed that the absolute right of ijbar thereafter should no longer be exercised in Indonesia after the birth of the Marriage Law and the Compilation of Islamic Law. From a number of chapters it is clear that the permission of the bride and groom, or prospective husband and wife, is an important component of the marriage itself. The concept of ijbar has a legal basis in fiqh, fiqh experts have different opinions about forced marriage (ijbar). Center for Women's Studies UIN Sunan Kalijaga provides two types of legal protection for women whose human rights are violated because of marriage with ijbar rights from the point of view of Islamic law. First, every woman has the same right to choose her partner. Second, a woman may ask her guardian's permission to marry her without his knowledge or consent.